Resurrection man - McNamee, Eoin 1961- (Picador, 1995)
In Belfast, the story of a killer, a psychopath who kidnaps Catholics in the streets to carve them up with his knife. For a while he and his gang serve the purpose of higher interests, then he becomes a liability and the time comes to get rid of him. A first novel.
Keywords: Ulster Volunteer Force; City and town life -- Fiction; Criminals -- Fiction; Mörder; Belfast (Northern Ireland) -- Fiction; Belfast; Fiktionale Darstellung; Psychological fiction